Social roles in emerging adulthood. Results of a nationwide study - Anna Walczak (Studia z Teorii Wychowania)
The article attempts to present emerging adulthood, i.e. experiences during the transition from adolescence to full adult status from the perspective of the social role theory. The empirical basis is survey research carried out on a random, nationwide sample of people aged 18-29 (n=303), stratified by gender and size of the town. The aim of the analysis is to answer questions about identification with roles, and changing the complexity of roles depending on age, gender, and self-identification with the status of an adult. The results indicate that in the period of emerging adulthood, the professional role becomes particularly important, and the set of roles related to the status of an adult overshadows the roles typical of adolescence. In addition, it has been shown that women identify with more roles than men and more often include the parental role and the role of wife/partner in the set of roles.